2023
DOI: 10.3390/antiox12040856
|View full text |Cite
|
Sign up to set email alerts
|

The 4-Hydroxynonenal–Protein Adducts and Their Biological Relevance: Are Some Proteins Preferred Targets?

Abstract: It is well known that oxidative stress and lipid peroxidation (LPO) play a role in physiology and pathology. The most studied LPO product with pleiotropic capabilities is 4-hydroxynonenal (4-HNE). It is considered as an important mediator of cellular signaling processes and a second messenger of reactive oxygen species. The effects of 4-HNE are mainly attributed to its adduction with proteins. Whereas the Michael adducts thus formed are preferred in an order of potency of cysteine > histidine > lysine ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 148 publications
0
24
0
Order By: Relevance
“…However, this is based on structural considerations as lysines are typically more abundant in proteins than histidines or cysteines. From a reactivity point of view, Cys » His > Lys > Arg [ 58 ]. Thus, in a model peptide containing Cys, His and Lys residues, Cys will be preferentially targeted in terms of reactivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is based on structural considerations as lysines are typically more abundant in proteins than histidines or cysteines. From a reactivity point of view, Cys » His > Lys > Arg [ 58 ]. Thus, in a model peptide containing Cys, His and Lys residues, Cys will be preferentially targeted in terms of reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the study by Hacker et al [ 61 ], our modeling studies showed that a stronger binding of the truncated PE species to proteins correlated with the number of electrophilic amino acids in general (K, H and C). In terms of chemical reactivity, however, Cys residues are far more reactive than His, Lys or Arg residues [ 58 ]. Along these lines, our peptide model system data suggested that Cys was the preferred residue for adduction with the highly reactive PE(26:2)+2 oxygens or PE-(18:0/hydroxy-8-oxo-oct-6-enoic acid (HOOA)) truncated species.…”
Section: Discussionmentioning
confidence: 99%
“…A pivotal aspect to delve into more thoroughly involves examining redox signaling and processes associated with lipid peroxidation that coincide with the observed alterations in the activity and expression of the antioxidant enzymes investigated in this study. In this context, the scrutiny of 4-HNE, a prominent marker of lipid peroxidation and a crucial molecule in redox signaling, may yield significant insights essential for a comprehensive understanding of the reported observations.…”
Section: Discussionmentioning
confidence: 99%
“…Fish eyes are known to have very high levels of PUFA, thus putting the eye at risk of oxidative stress and damage related to lipid peroxidation (Brodtkorb et al, 1997;Waagbø et al, 2003). Excess levels of 4-HNE react with and modify nucleophilic amino acid residues of proteins, forming protein adducts of various sizes (Andringa et al, 2014;Li et al, 2022;Milkovic et al, 2023). 4-HNE adduction can alter and impair protein function, which can potentially disrupt cellular and biological processes, and can be very toxic to surrounding cells or tissues (Marques et al, 2004;Milkovic et al, 2023).…”
mentioning
confidence: 99%
“…Excess levels of 4-HNE react with and modify nucleophilic amino acid residues of proteins, forming protein adducts of various sizes (Andringa et al, 2014;Li et al, 2022;Milkovic et al, 2023). 4-HNE adduction can alter and impair protein function, which can potentially disrupt cellular and biological processes, and can be very toxic to surrounding cells or tissues (Marques et al, 2004;Milkovic et al, 2023). 4-HNE has been shown to induce cataract in rat lenses in organ culture (Ansari et al, 1996;Srivastava et al, 1996).…”
mentioning
confidence: 99%